RELATIONSHIP BETWEEN MALL ATTRIBUTES, COSTUMER SATISFACTION AND POSITIVE WORD-OF-MOUTH SKA PEKANBARU - Dian Martha Darman; Fajar Restuhadi; Rosnita Rosnita (UIR Press, 2018)
SKA mall was one of the biggest malls in Pekanbaru. SKA mall has many costumers who come from Pekanbaru and also outside Pekanbaru. This mall is also considered as one of the most favourite destinations for visitors froms outside of Pekanbaru. This study aimed to find out how the relationship between the five mall attributes (mall environment, convenience, retailers, rewards and quality of service) to the satisfaction of mall SKA Pekanbaru consumers and to know how customer satisfaction relates to positive word-of-mouth over mall SKA Pekanbaru. This study uses the online survey method on 160 respondents. Considerations in determining respondents were those visitors from outside of Pekanbaru and had visited the SKA Mall more than once. The analysis used in this study was the SEM method. The results showed that only retailers had positive and significant correlation with positive WOM through customer satisfaction, comfort and reward variables had a positive but not significant correlation. While the mall environment variable and mall service quality did not have a correlation with positive WOM through customer satisfaction. There was a strong correlation between consumer satisfaction and positive word of mouth, according to the theory that consumer satisfaction was one factor than positive word-of-mouth